Integration of transcriptomic and metabonomic reveals molecular differences of sweetness and aroma between postharvest and vine ripened tomato fruit. (September 2022) - Min, Dedong; Li, Zilong; Fu, Xiaodong; Wang, Jihan; Li, Fujun; Li, Xiaoan; Zhang, Xinhua
Abstract: The quality of vine ripened (PR) fruit is better than that of postharvest ripened (VR) fruit, which is reflected in taste and aroma. The results indicated that there was a remarkable increase in soluble sugars (sucrose, fructose, and glucose) and volatile organic compounds (VOCs) contents during the process of maturity. At the full red stage, VR fruit possessed higher soluble sugars and VOCs contents, especially (E)-2-Octenal, 6-methyl-5-Hepten-2-one, 6, 10-dimethyl-5, 9-Undecadien-2-one trans -β-Ionone, methyl salicylate, compared to PR fruit, which partly explained why VR fruit has better flavor quality. The transcriptome analysis indicated that 4989 and 4847 differentially expressed genes (DEGs) were up- and down-regulated in PR vs. VR, respectively. These DEGs participated in multiple metabolic pathways related to sugar and VOCs metabolism. Moreover, MYB transcription factors were critical in sugar metabolism. And, seven hub genes were found which played key roles in the regulation of fruit flavor. These results laid a foundation for the flavor research of postharvest fruit and enhanced our understanding of the differences in flavor, especially sweetness and aroma between PR and VR fruit. Highlights: The soluble sugars contents were higher in VR fruit than those in PR fruit. The volatile compounds contents were higher in VR fruit than those in PR fruit. Expressions of genes related to sugar metabolism are up-regulated in VR fruit. Expressions of genes related to volatile compounds metabolism are induced in VR fruit.